Donor-Derived Human Parvovirus B19 Infection in Kidney Transplantation - Yu, Yedong; Wei, Chunchun; Lyu, Junhao; Wu, Xiaoliang; Wang, Rending; Huang, Hongfeng; Wu, Jianyong; Chen, Jianghua; Peng, Wenhan (Frontiers in Cellular and Infection Microbiology, 2021)
Background Donor-derived human parvovirus B19 (B19V) infections are rarely reported. Thus, its incidence in kidney transplantation is still unknown due to lack of surveillance studies. Similarly, whether the donor needs to be routinely screened for B19V and whether the kidneys from those with B19V DNAemia could be accepted also remain unknown. Methods This retrospective study aims to evaluate the donor-derived B19V infections occurring in 823 living and 1,225 deceased donor kidney transplantations from January 2016 to December 2020. The serum viral load of living donors and their corresponding recipients was evaluated before and after transplantation. Meanwhile, for the deceased donor kidney transplantation, the serum viral load of recipients was only tested after transplantation; if recipients of a deceased donor subsequently developed B19V infection, the serum viral load of recipients and their corresponding donors before transplantation would then be further traced. Results A total of 15 living donors were B19V DNAemia positive before the donation, of which B19V DNAemia occurred in three corresponding recipients. In deceased donor kidney transplantation, DNAemia occurred simultaneously in 18 recipients and their corresponding nine donors. A progressive decline in hemoglobin and reticulocyte count could be observed in one living donor recipient and other 11 deceased donor recipients, which were all well controlled by treatment eventually. Conclusion The incidence of donor-derived B19V infection was 0.4% and 1.5% in living and deceased kidney transplantations, respectively. B19V was seemingly unnecessary to be routinely screened for the donor. Moreover, kidneys of the donors with B19V infection were acceptable.